Predictive Analytics with Categorical Data: Advanced Regression Methods for Real-World Applications. - Buscha, Franz (linkedin.com, 2024)
Explore how to analyze and interpret categorical data using multivariate regression models, as well as model outcomes like customer choice, health status or survey responses.